2006
DOI: 10.1016/j.intcom.2006.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Homepage aesthetics: The search for preference factors and the challenges of subjectivity

Abstract: While many studies have considered the usability of website homepages, subjective issues such as preference have been under explored. This paper describes a pilot study that investigates subjects' preferences for different homepages. The study applies Berlyne's theory of experimental aesthetics to website homepages. This theory suggests that there is an inverted-U shape relationship between preference for a stimulus and its complexity. Twelve subjects evaluated 12 homepages. The study used a ranking method to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 22 publications
5
45
0
Order By: Relevance
“…The results of the present study suggest that websites perceived as low in complexity elicit higher levels of aesthetic appreciation than those that are more visually complex, supporting a growing amount of research that documents a negative relationship [25,28,39,40]. A key feature of working memory may help to elucidate the impact of complexity on felt aesthetics.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…The results of the present study suggest that websites perceived as low in complexity elicit higher levels of aesthetic appreciation than those that are more visually complex, supporting a growing amount of research that documents a negative relationship [25,28,39,40]. A key feature of working memory may help to elucidate the impact of complexity on felt aesthetics.…”
Section: Discussionsupporting
confidence: 74%
“…That is, the optimum level of aesthetic pleasure corresponds with the lowest degree of perceived complexity. For instance, Pandir and Knight [28], finding no support for Berlyne's theory of aesthetics, discovered a significant negative correlation between pleasure and complexity elicited from the perception of websites. Tuch, Bargas-Avilaa, Opwis, and Wilhelm [39] further uncovered a negative relationship between complexity and affective valence, and in addition, found that recognition performance is best with websites of low complexity.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Switching costs have been studied broadly in the service sectors; 8 however, there are some major differences in nature between online services and offline services, such as the restrictions of operation time and its location (Yen, 2010). According to Pandir and Knight (2006), a key way of achieving that is through the homepage design. In fact, previous studies have suggested that visual appearance is extremely important in users' preferences (Shenkman and Jonsson, 2000;Kim and Niehm, 2009), and that consumers prefer beautiful websites, perceiving them even as more usable.…”
Section: Website Imagementioning
confidence: 99%